Half-Widows: Invisible Victims of the Enforced Disappearances and Their Status in Kashmir. Issue 2 (December 2019) - Singh, Kislay Kumar
The disappearance of young men in on-going armed conflict over the last 3 decades in Kashmir has given birth to a new identity to the women. This identity is called half-widows. The term, half-widows, signifies those women whose husbands have disappeared in armed conflict but are not declared dead yet. Men are directly involved in the armed conflicts and are the direct victims of it, but women are the ones who have been going through all the consequences of armed conflict. This article contextualizes the phenomenon of enforced disappearance in Kashmir and its grave consequences on women. Based on the qualitative case-study approach, 15 half-widows were interviewed in 2017 to examine their social, economic and psychological problems. Information from secondary sources was also incorporated.